STUDI PENENTUAN SUMUR RESAPAN SEBAGAI UPAYA PENGENDALIAN BANJIR DI KOTA PEKALONGAN BERBASIS SISTEM INFORMASI GEOGRAFIS - Putranto, Thomas Triadi; Hadiyanto, Hadiyanto; Hati, Asri Cahaya (BAPPEDA Kota Pekalongan, 2020)
Population and socio-economic growth trigger changes in land use functions. Land use and climate change in line with the increase in the rate of surface water and a decrease in the quality of water infiltration into the soil. Decreasing water absorption triggers an abundance of water on the surface which leads to hydrometeorological disasters, one of them is flooding. The research study is in Pekalongan City which has a very flat topography a nd the estuary area of several rivers from the upstream area. The current condition of Pekalongan City has a huge potential for flood disaster. The purposes of this study are to measure the depth of the groundwater level, to delineate the flooding area, and to recommend the infiltration wells based on the Geographic Information System. The methods were hydrogeological mapping, including the measurement of the water table, collecting land use maps, delineating flooding zone, calculating impermeable zones, collecting hydrological data such as precipitation . The results show that the groundwater level at the research location is classified into 3 classes, namely 0 -1.5 meters, 1.5-3 meters, and > 3 meters. The need for infiltration wells in the flood-prone areas of Pekalongan City is 57,718 units. The needs for rainwater infiltration wells in areas outside flood -prone areas and groundwater depth> 1.5 meters are 227,416 units with a well's depth between 1.5 to 4 meters. Keywords: Infiltration well, hydrometeorological, disaster Pekalongan City